2020
DOI: 10.20538/1682-0363-2020-2-63-71
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional characteristics of retrosternal adipose tissue and their relation to arterial stiffness parameters in patients after coronary artery bypass grafting

Abstract: Цель-исследование морфофункциональных характеристик адипоцитов загрудинной жировой ткани (ЗЖТ) в сравнении с другими типами жировой ткани (ЖТ), а также изучение их связи с показателями артериальной жесткости у пациентов с коронарным атеросклерозом, подвергшихся операции аортокоронарного шунтирования (АКШ). Материалы и методы. В настоящее пилотное исследование включены 17 пациентов (12 мужчин и 5 женщин) в возрасте 40-70 лет со стабильной ишемической болезнью сердца и документированным коронарным атеросклерозом… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our previous studies, we have demonstrated interconnection between the secretory activity of thymic adipose tissue and arterial vascular stiffness. Parameters of vascular stiffness were directly related to the degree of leptin secretion by thymic adipocytes and, indirectly, to insulin secretion [48].…”
Section: Thymus and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we have demonstrated interconnection between the secretory activity of thymic adipose tissue and arterial vascular stiffness. Parameters of vascular stiffness were directly related to the degree of leptin secretion by thymic adipocytes and, indirectly, to insulin secretion [48].…”
Section: Thymus and Atherosclerosismentioning
confidence: 99%
“…The summarized evidence of the protective functions of thymus in atherosclerosis is summarized in Table 1. [48] ApoB-apolipoprotein B; CABG-coronary artery bypass graft; CAD-coronary artery disease; CD-cluster of differentiation; HDL-C-high-density lipoproteins cholesterol; IFN-interferon; IL-interleukin; NSTACS-non-ST elevation acute coronary syndrome; TGF-transforming growth factor; TNF-tumor necrosis factor; Treg-T regulatory lymphocytes.…”
Section: Thymus and Atherosclerosismentioning
confidence: 99%